PENATAAN PERMUKIMAN PASCA BENCANA ALAM DI DESA PANJANGREJO KABUPATEN BANTUL: Kajian Tingkat Partisipasi Masyarakat dan Ketercapaian Pembangunan - Setiadi, Amos; Rudwiarti, Lucia Asdra; Langer, Isak Jonathan; Widhiari, Luh Putu (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Panjangrejo Village is one of Yogyakarta 2006 Earthquake’s epicentrums. For that matter, evaluating its housing’s post-disaster rehabilitation is essential, considering its impacts in the future. Housing rehabilitation encompasses infrastructure whose planning was done by employing participation approach so as to achieve the target as has been planned. In the planning stage, the residents were entitled to participate in mapping and identifying the area’s potentials and resources. This research employed a qualitative-descriptive method by studying the Rencana Penataan Permukiman Desa Panjangrejo (Panjangrejo Village Housing Plan). The document was evaluated regarding the participation approach it employed and its target development. This research focused on addressing the issues of: “whether or not this approach has accommodated residents’ aspirations in formulating the infrastructure development policy based on the village’s potentials and priority” and “whether or not the rehabilitation and reconstruction have been done sistematically and in an integrated manner”. The investigation has found out that the residents’ aspirations were accommodated during the publicising, planning and organising stages. The rehabilitation and reconstruction have resulted in high quality infrastructure as it fulfills the standard of requirement and was organised sistematically and in an integrated manner. At the same time, quantitatively, the building went beyond the target plan.